Influence of light and plant size on the reproduction and growth of small palm tree species: Comparing two methods for measuring canopy openness - Amadeu, Luã S. N.; Sampaio, Mauricio B.; dos Santos, Flavio A. M. (American journal of botany, 2016)
PREMISE OF THE STUDY: The reproduction and growth of large palms are influenced by many factors, including light and plant size, but few studies have examined smaller species (up to 2 m tall). We examined the effect of incident light and individual size on growth rates, the probability of reproduction, and the number of inflorescences of three small palm species and compared two methods for estimating canopy openness. METHODS: We measured canopy openness above the crowns of 132 adult plants and in the centers of 72 subplots (10 × 10 m) where individuals were sampled. We also recorded individual size and the number of leaves and inflorescences produced in two years. KEY RESULTS: Reproductive individuals of Butia paraguayensis tend to occur in illuminated microhabitats. Reproduction of Acrocomio emensis was correlated with stem diameter, but not with light. Reproduction was inversely related to individual size and light in Syagrus petraea, probably because this clonal palm invests heavily in sexual reproduction during its younger stages and clonal activity in older stages and may be adapted to the low-light conditions of the woodland understory. Growth was not predicted by light or individual size. Stronger correlations were found when incident light was measured directly above the crown, as opposed to the subplot center. CONCLUSIONS: The influences of light on reproduction are dependent on plant life histories, even among related and sympatric species. Light measurements directly above individual crowns provide better understanding of the reproductive effort rather than in subplot center.